2017
DOI: 10.1007/s00213-017-4804-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensitivity to reinforcement in adolescent compared to adult Sprague-Dawley rats of both sexes

Abstract: RATIONALE: Adolescence is a period of considerable development of brain and behavior and is the time during which most drug use is initiated. OBJECTIVE: Age-dependent differences in motivated behaviors may be one of the factors that contribute to heightened vulnerability to developing substance use disorders, so we sought to compare age differences in methamphetamine (METH) and saccharin seeking. METHODS: Beginning during adolescence or adulthood, male and female Sprague-Dawley rats were trained to self-admini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 86 publications
4
17
2
Order By: Relevance
“…Despite evidence for a peri/post-pubertal peak in reward consumption (Friemel et al, 2010;Marshall et al, 2017), motivation (Friemel et al, 2010), and cocaine self-administration in males (Wong, Ford, Pagels, McCutcheon, & Marinelli, 2013), several studies measuring instrumental responding for non-drug reinforcers report either comparable responding (Sturman & Moghaddam, 2011;Kim, Simon, Wood, & Moghaddam, 2016;Naneix, Marchand, Di Scala, Pape, & Coutureau, 2012) or decreased responding in adolescents compared to adults (present study; Andrzejewski et al, 2011;Sturman et al, 2010;Hankosky et al, 2017). One factor that could contribute to the apparent discrepancies between reward consumption and instrumental responding is whether the measure accounts for differences in body weight.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Despite evidence for a peri/post-pubertal peak in reward consumption (Friemel et al, 2010;Marshall et al, 2017), motivation (Friemel et al, 2010), and cocaine self-administration in males (Wong, Ford, Pagels, McCutcheon, & Marinelli, 2013), several studies measuring instrumental responding for non-drug reinforcers report either comparable responding (Sturman & Moghaddam, 2011;Kim, Simon, Wood, & Moghaddam, 2016;Naneix, Marchand, Di Scala, Pape, & Coutureau, 2012) or decreased responding in adolescents compared to adults (present study; Andrzejewski et al, 2011;Sturman et al, 2010;Hankosky et al, 2017). One factor that could contribute to the apparent discrepancies between reward consumption and instrumental responding is whether the measure accounts for differences in body weight.…”
Section: Discussioncontrasting
confidence: 62%
“…Studies of reward consumption and drug self-administration adjust for differences in body weight, while measures of instrumental responding for non-drug reinforcers typically do not. As such, studies of sex differences in non-drug reward processing have found that females consume more reward per body weight when given ad libitum access (present study; Marshall et al, 2017;, but seem to respond for reinforcer similarly or more than males (present study; Hankosky et al, 2017) depending on whether the measure is normalized to body weight. In the present study, as the adolescents increase in body size across RI-30 sessions, they increase their responding in order to maintain their elevated reinforcement rate (adjusted for body weight) relative to adults.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Subjects were a total of 82 Sprague-Dawley rats (32 male, 50 female) that had previously been trained to self-administer d -methamphetamine HCl (0.08 mg/kg) or received non-contingent infusions of saline beginning during either adolescence or adulthood. The full methods outlining treatment of the METH rats used in this study and analysis of age- and sex-differences in METH self-administration was reported previously (Hankosky et al, 2018). Of the 46 rats that initiated METH self-administration, 15 males and 25 females met acquisition criteria to be included in this study.…”
Section: Methodsmentioning
confidence: 99%